2004
DOI: 10.1159/000080241
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial on the Efficacy and Safety of Atorvastatin in Patients with Type 2 Diabetes on Hemodialysis (4D Study): Demographic and Baseline Characteristics

Abstract: Patients with type 2 diabetes on dialysis are at a substantially increased risk of cardiovascular and cerebrovascular diseases. Dyslipidemia characterized by moderately elevated low-density lipoprotein cholesterol and high triglycerides and low high-density lipoprotein cholesterol levels is common in this population. We hypothesized that 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors would reduce vascular morbidity and mortality in this patient group. The ‘Deutsche Diabetes Dialyse Studie’ (4D stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(106 citation statements)
references
References 41 publications
4
98
2
2
Order By: Relevance
“…In a large study of type 2 diabetic patients undergoing haemodialysis (4D study) Wanner and colleagues found a history of myocardial infarction, CABG or PCI in 23% and a history of stroke in 18% [5]. These frequencies are slightly lower than those found in the present study.…”
Section: Diabetic Complications and Cardiovascular Diseasescontrasting
confidence: 83%
See 1 more Smart Citation
“…In a large study of type 2 diabetic patients undergoing haemodialysis (4D study) Wanner and colleagues found a history of myocardial infarction, CABG or PCI in 23% and a history of stroke in 18% [5]. These frequencies are slightly lower than those found in the present study.…”
Section: Diabetic Complications and Cardiovascular Diseasescontrasting
confidence: 83%
“…Although the survival of diabetic patients treated with dialysis in Denmark has improved during the past 15 years [4], a significant number of diabetic patients treated with chronic maintenance dialysis still suffer from one or more diabetic complications besides the kidney failure and have increased cardiovascular morbidity and mortality rates [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Design and methods of the 4D Study have previously been reported (11,12). The 4D Study was a randomized, multicenter trial of 1255 patients who had type 2 diabetes, were 18 to 80 years of age, and had a previous duration of hemodialysis of Ͻ2 years.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…End points were evaluated by a specialized committee blinded to study treatment, according to prespecified criteria (11)(12)(13). The primary study outcome was a composite of death from cardiac causes, myocardial infarction (MI), and stroke, whichever occurred first (composite cardiovascular end point [CVE]).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…15 A late amendment during the final recruitment period of the trial added stroke as a component of the primary endpoint. 16,17 Separate analysis of cardiac endpoints in the 4D study showed a significant risk reduction of events in the atorvastatin arm as compared with placebo. 16 Based on these findings from the 4D we hypothesized, before unblinding of the AURORA trial, that rosuvastatin might reduce the risk of coronary events in diabetic patients.…”
mentioning
confidence: 99%